UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA MATERI PENYAJIAN DATA MELALUI “DATAQUEST GAMES” KELAS 3 SDN SUKUN 2 KOTA MALANG - Fitrah, Adinda; Andika Gutama; Ahmad Rifky Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The study aims to improve mathematics learning outcomes in the material of data presentation in tables through Dataquest Games activities in the form of data adventure missions based on a cooperative learning model of the team quiz type. This study uses the Classroom Action Research (CAR) method which is implemented in two cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The research subjects were 28 students in class III-A at SDN Sukun 2 Malang City. Data collection techniques were carried out through interviews, observation, documentation, and learning outcome tests and data were analyzed using quantitative and qualitative descriptive techniques. The implementation of learning with the concept of learning posts in groups. Each post contains different data presentation challenges, such as reading tables, grouping data, making simple diagrams and solving data presentation problems. The results of the study showed an increase in student learning outcomes in each cycle. In cycle I, the average student learning outcomes reached 82.1 with a completion percentage of 78% and was in the sufficient category. In cycle II, the average learning outcomes increased to 91.8 with a completion percentage of 93% and was in the very good category. Dataquest Games activities can increase student engagement, cooperation, self-confidence, and enthusiasm during the learning process. Therefore, this game can be used as an innovative learning alternative for data presentation in elementary schools.